2022
DOI: 10.18326/ijip.v4i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Empowerment on Innovative Behavior with Transformational Leadership Style as Moderator Variable

Abstract: State-Owned Enterprises (BUMN) is a company that has a role as an agent of value crator and agent of development. So what must be done is to improve the performance of BUMN, restructure BUMN and establish new BUMN. In achieving its goals, this role must be realized by carrying out a high innovation from every individual who is in a company. In terms of increasing Psy, an application of psychological empowerment is needed in the company and moderated by leaders who have a Transformational Leadership Style. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was concluded that the psychological empowerment of the faculty members had a positive and significant effect on their change orientation levels. One significant reason for the emergence of innovative behavior is said to be psychological empowerment (Priyatama et al, 2022), which enables faculty members to see their work as meaningful and to have more information about the job. The amount and quality of the information provided can therefore affect how individuals respond to change (Oreg, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the psychological empowerment of the faculty members had a positive and significant effect on their change orientation levels. One significant reason for the emergence of innovative behavior is said to be psychological empowerment (Priyatama et al, 2022), which enables faculty members to see their work as meaningful and to have more information about the job. The amount and quality of the information provided can therefore affect how individuals respond to change (Oreg, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study is to investigate the connection between PE and IWB, which has gained attention in recent literature (Priyatama et al ., 2022). Our hypothesis suggests that there is a positive correlation between PE and IWB.…”
Section: Introductionmentioning
confidence: 99%